The impact of new ways of working on organizations and employees: A systematic review of literature - Karine Renard; Frederic Cornu; Yves Emery; David Giauque (Administrative Sciences, 2021)
A new research stream emerged in the 2000s dedicated to flexible work arrangements in public and private organizations, called "new ways of working" (NWW). This article aims to examine NWW from both a theoretical and empirical perspective, focusing on definitional issues as well as on HR outcomes of this new concept. Current definitions of NWW are manifold and based on rather vague theoretical foundations. As NWW outcomes may be both positive and/or negative, we mobilize the "mutual gains" vs. "conflicting outcomes" theoretical debate to discuss the results of our literature review. This review is based on 21 articles (out of 90 initially selected for eligibility) dealing with NWW as a concept or as a bundle of practices. Findings demonstrate that NWW definitions are diverse and somewhat imprecise, lacking theoretical foundations and leading to fragmented research designs and findings. Findings also highlight the current lack of empirical data, which therefore does not allow any real conclusions on NWW's effects on employees' and organizations' well-being and performance.
Keywords: 350; activity-based offices; flexible work arrangements; flextime; knowledge workers; new ways of working; telework